2015
DOI: 10.1140/epjc/s10052-015-3734-9
|View full text |Cite
|
Sign up to set email alerts
|

Accretion processes for general spherically symmetric compact objects

Abstract: We investigate the accretion process for different spherically symmetric space-time geometries for a static fluid. We analyze this procedure using the most general black hole metric ansatz. After that, we examine the accretion process for specific spherically symmetric metrics obtaining the velocity of the sound during the process and the critical speed of the flow of the fluid around the black hole. In addition, we study the behavior of the rate of change of the mass for each chosen metric for a barotropic fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 38 publications
7
59
0
Order By: Relevance
“…The value of ω represent the various models of DE such that for cosmological constant ω = 1, dust ω = 0, stiff ω = −1, phantom energy ω < −1 and quintessence −1 < ω < 1. It is noted that the behavior of velocity is similar to those reported in [41,42]. Also, we have found that velocity is positive for ω ≥ −0.5 and negative for phantom energy (ω < Figure 3 shows the rate of change of RBH mass for different value of ω.…”
Section: Nonminimal Magnetically Charged Rbhsupporting
confidence: 83%
See 3 more Smart Citations
“…The value of ω represent the various models of DE such that for cosmological constant ω = 1, dust ω = 0, stiff ω = −1, phantom energy ω < −1 and quintessence −1 < ω < 1. It is noted that the behavior of velocity is similar to those reported in [41,42]. Also, we have found that velocity is positive for ω ≥ −0.5 and negative for phantom energy (ω < Figure 3 shows the rate of change of RBH mass for different value of ω.…”
Section: Nonminimal Magnetically Charged Rbhsupporting
confidence: 83%
“…Also, we have found that velocity is positive for ω ≥ −0.5 and negative for phantom energy (ω < Figure 3 shows the rate of change of RBH mass for different value of ω. In this case, the profile of accreting mass of nonminimal RBH is similar to the profile for charged BH in string theory [41], which shows that the mass of RBH as a result of accretion of dust, stiff and quintessence matter increases and reverse case will be occur for phantom energy.…”
Section: Nonminimal Magnetically Charged Rbhsupporting
confidence: 58%
See 2 more Smart Citations
“…This process may be described by a perfect fluid coupled to general relativity representing a plasma which obeys the equations of ideal or resistive magnetohydrodynamics or a fluid coupled to radiation. Such accretion processes along with their detailed physical descriptions, can be found in [67] and references therein, see also [68][69][70][71][72][73][74][75]. On the other hand, there are also other kind of accretion processes related to the black holes surrounded by exotic matter fields as potential models of dark energy, whose existence and features are motivated by the problems in the standard model of cosmology.…”
Section: Introductionmentioning
confidence: 99%